(untitled) (KULT_online, 2019)
This volume is devoted to exploring relationships between literature and work, two terms that assume a variety of meanings amongst the individual contributions. It is comprised of undergraduate and graduate student papers first presented at the 7th Student Congress of Comparative Studies at Ludwig Maximilian University Munich and characterized by a high degree of eclecticism, with articles ranging from Plato’s notions of work and ‘the work’ in his literary criticism, to analyses of work in pirate fiction after 1700, to ‘work on myth’ in contemporary popular culture. While the variety of topics and case studies has a somewhat dizzying effect, each individual article is clear and compellingly argued. A highlight is Wolfram Ette’s concise introduction on groundbreaking theoretical contributions to the topic.